Implication of Dietary Iron-Chelating Bioactive Compounds in Molecular Mechanisms of Oxidative Stress-Induced Cell Ageing - Alexandra Barbouti; Nefeli Lagopati; Dimitris Veroutis; Vlasios Goulas; Konstantinos Evangelou; Panagiotis Kanavaros; Vassilis G. Gorgoulis; Dimitrios Galaris (MDPI AG, 2021)
One of the prevailing perceptions regarding the ageing of cells and organisms is the intracellular gradual accumulation of oxidatively damaged macromolecules, leading to the decline of cell and organ function (free radical theory of ageing). This chemically undefined material known as "lipofuscin," "ceroid," or "age pigment" is mainly formed through unregulated and nonspecific oxidative modifications of cellular macromolecules that are induced by highly reactive free radicals. A necessary precondition for reactive free radical generation and lipofuscin formation is the intracellular availability of ferrous iron (Fe2+) ("labile iron"), catalyzing the conversion of weak oxidants such as peroxides, to extremely reactive ones like hydroxyl (HO•) or alcoxyl (RO•) radicals. If the oxidized materials remain unrepaired for extended periods of time, they can be further oxidized to generate ultimate over-oxidized products that are unable to be repaired, degraded, or exocytosed by the relevant cellular systems. Additionally, over-oxidized materials might inactivate cellular protection and repair mechanisms, thus allowing for futile cycles of increasingly rapid lipofuscin accumulation. In this review paper, we present evidence that the modulation of the labile iron pool distribution by nutritional or pharmacological means represents a hitherto unappreciated target for hampering lipofuscin accumulation and cellular ageing.